2015
DOI: 10.3390/molecules20022510
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glycosaminoglycans (GAGs) on Amyloid Aggregation and Toxicity

Abstract: Amyloidosis is a protein folding disorder in which normally soluble proteins are deposited extracellularly as insoluble fibrils, impairing tissue structure and function. Charged polyelectrolytes such as glycosaminoglycans (GAGs) are frequently found associated with the proteinaceous deposits in tissues of patients affected by amyloid diseases. Experimental evidence indicate that they can play an active role in favoring amyloid fibril formation and stabilization. Binding of GAGs to amyloid fibrils occurs mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
108
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 115 publications
5
108
0
4
Order By: Relevance
“…8C, bottom panel, lanes 1-3). When treating soluble sCT with trypsin, no peptide was retained in the gel (data not shown), most likely reflecting the small size of tryptic products sCT(1-11), sCT (12)(13)(14)(15)(16)(17)(18), sCT (19 -24), and sCT (25)(26)(27)(28)(29)(30)(31)(32). For sCT-OH, trypsin digestion of fibrils gave results identical to those presented here for sCT-NH 2 (data not shown).…”
Section: Heparin-free Sct Fibrils Are Able To Bind Tht When Titratedsupporting
confidence: 72%
See 3 more Smart Citations
“…8C, bottom panel, lanes 1-3). When treating soluble sCT with trypsin, no peptide was retained in the gel (data not shown), most likely reflecting the small size of tryptic products sCT(1-11), sCT (12)(13)(14)(15)(16)(17)(18), sCT (19 -24), and sCT (25)(26)(27)(28)(29)(30)(31)(32). For sCT-OH, trypsin digestion of fibrils gave results identical to those presented here for sCT-NH 2 (data not shown).…”
Section: Heparin-free Sct Fibrils Are Able To Bind Tht When Titratedsupporting
confidence: 72%
“…Over this pH interval, the charge of sCT will change by up to 1.3 units (see below), and this will affect interactions with the highly anionic GAG molecules. To investigate the role of charge in these interactions, we used the following three variants of sCT: 1) the natural form, which is C-terminally amidated (sCT-NH 2 ) and goes from a net charge of approximately ϩ3.9 at pH 5.5 to approximately ϩ2.6 at pH 7.4 based on conventional pK a value calculations; 2) a form with a free C-terminal carboxylate group (sCT-OH), which will be anionic above approximately pH 4, going from a net charge of ϩ2.9 at pH 5.5 to ϩ1.6 at pH 7.4; and 3) the mutant His 17 3 Ala (sCTH17A-OH; with a free C-terminal carboxylate group), which removes the only side chain that titrates over the pH interval 7.4 -5.5 so that the net charge of this mutant only decreases by 0.6 unit from ϩ2.1 at pH 5.5 to ϩ1.5 at pH 7.4.…”
Section: Sct and Heparin Form A Binding Complex With ␣-Helicalmentioning
confidence: 99%
See 2 more Smart Citations
“…These linear and unbranched polysaccharides are ubiquitously associated with amyloid deposits D r a f t 5 linked to protein misfolding diseases (Iannuzzi et al 2015), including those from TTR (Inoue et al 1998), Aβ (DeWitt et al 1993, IAPP (Young et al 1992), β2-microglobulin (Ohishi et al 1990) and immunoglobulin light chain (Stenstad et al 1991). These studies have suggested a causative role of sulfated GAGs in the fibrillogenesis and deposition of a variety of amyloidogenic polypeptides and have prompted biophysical investigations.…”
Section: Glycosaminoglycans: Promotors Of Amyloid Assemblymentioning
confidence: 99%